Retirement from elite sport and self-esteem: a longitudinal study over 12 years - Schmid, Jürg; Conzelmann, Achim; Engel, Robertino; Kuettel, Andreas; Schmid, Michael J. (Frontiers in Psychology, 2023)
This study examined the complex associations between athletic retirement and self-esteem among former elite athletes. With reference to theoretical and empirical work on the quality of the transition out of sport, information was collected from 290 (junior) elite athletes in a retrospective-prospective design: At the first measurement, active athletes assessed satisfaction with their sporting career, athletic identity, and self-esteem. At the second measurement (12 years later), the now former athletes rated transition characteristics of their career ending, sporting career success, emotional reactions to career termination, extent of necessary adjustment required following athletic retirement, duration and quality of adjustment, and self-esteem. Structural equation modelling revealed that neither sporting career success nor sporting career satisfaction had a direct effect on adjustment. However, athletic identity and retirement planning predicted the extent of adjustment, which in turn predicted the duration and quality of adjustment, and ultimately self-esteem. Voluntariness, timeliness, and perceptions of gain predicted emotional reactions towards career termination, which also predicted the duration of adjustment. Extent of adjustment and emotional reactions mediated between preconditions of career termination and transition characteristics and self-esteem. While self-esteem after career termination was predominantly predicted by self-esteem 12 years earlier, perceived quality of adjustment to career termination had a significant effect on self-esteem in the post-athletic career. These results complement existing literature illustrating that athletic retirement is a complex and dynamic process and the quality of this transition has a small, but still noteworthy effect on self-esteem, a central construct for well-being.